EXTREMELY FLUID BEHAVIOR OF HYDROUS PERALKALINE RHYOLITES - Dingwell D.B.; Hess K.U.; Romano C. (My University, 1998)
The viscosities of a series of water-bearing peralkaline rhyolitic melts have been experimentally determined. The dry melt compositions are composed of a series of additions of Na2O to a metaluminous base composition. The melts, initially hydrated at high pressures and quenched isobarically, have been prepared by cutting and polishing, then reheating across the glass transition at 1 atm where they are annealed to a relaxed metastable state and then investigated dilatometrically using micropenetration methods. The measurements have been performed in the viscosity range of 108.5-1011.5 Pa s which corresponds to temperatures in the range of 675-220°C for these compositions. Despite the relatively low viscosities of dry peralkaline melts in comparison with metaluminous melts of similar SiO2 content, the viscosities of peralkaline rhyolitic melts also decrease strongly and non-linearly with the addition of water. The resulting viscosity-temperature relationships for water-bearing peralkaline rhyolitic melts are shifted to much lower temperatures such that glass transition temperatures for moderate cooling rates correspond to extraordinarily low temperatures. A model is presented for the calculation of melt viscosities in the range of 108.5-1011.5 Pa s for peralkaline rhyolites with up to 7 wt% H2O. The very fluid nature of these peralkaline rhyolites over a wide range of water contents may facilitate a very efficient degassing history of glassy peralkaline rhyolites in nature. Efficient degassing might explain the apparent contradiction of the presence of common water-rich melt inclusions in phenocryst phases hosted in water-free glassy rhyolites, versus the absence of vesicular layers or textural evidence for a vesicular past for the glassy rocks.
Keywords: RHYOLITES; PERALKALIC COMPOSITION; WATER; MELTS; VISCOSITY; PLASTIC FLOW; MODELS